Biocompatible Heterogeneous Packaging and Laser-Assisted Fluid Interface Control for In Situ Sensor in Organ-on-a-Chip - Yu-Hsuan Lin; Shing-Fung Lau; Yen-Pei Lu; Kuo-Cheng Huang; Chien-Fang Ding; Yu-Hsiang Tang; Hsin-Yi Tsai (Micromachines)
The development of bionic organ-on-a-chip technology relies heavily on advancements in in situ sensors and biochip packaging. By integrating precise biological and fluid condition sensing with microfluidics and electronic components, long-term dynamic closed-loop culture systems can be achieved. This study aims to develop biocompatible heterogeneous packaging and laser surface modification techniques to enable the encapsulation of electronic components while minimizing their impact on fluid dynamics. Using a kidney-on-a-chip as a case study, a non-toxic packaging process and fluid interface control methods have been successfully developed. Experimentally, miniature pressure sensors and control circuit boards were encapsulated using parylene-C, a biocompatible material, to isolate biochemical fluids from electronic components. Ultraviolet laser processing was employed to fabricate structures on parylene-C. The results demonstrate that through precise control of processing parameters, the wettability of the material can be tuned freely within a contact angle range of 60° to 110°. Morphological observations and MTT assays confirmed that the material and the processing methods do not induce cytotoxicity. This technology will facilitate the packaging of various miniature electronic components and biochips in the future. Furthermore, laser processing enables rapid and precise control of interface conditions across different regions within the chip, demonstrating a high potential for customized mass production of biochips. The proposed innovations provide a solution for in situ sensing in organ-on-a-chip systems and advanced biochip packaging. We believe that the development of this technology is a critical step toward realizing the concept of “organ twin”.